Co‐insertion of Water with Protons into Organic Electrodes Enables High‐Rate and High‐Capacity Proton Batteries. Issue 3 (10th January 2023) - Su, Zhen; Tang, Jiaqi; Chen, Junbo; Guo, Haocheng; Wu, Sicheng; Yin, Songyan; Zhao, Tingwen; Jia, Chen; Meyer, Quentin; Rawal, Aditya; Ho, Junming; Fang, Yu; et al.
Abstract : The inherent short‐term transience of renewable energy sources causes significant challenges for the electricity grids. Energy storage systems that can simultaneously provide high power and high energy efficiency are required to accommodate the intermittent renewables. Herein, an ultrafast and high‐capacity aqueous proton battery is developed based on the organic pyrene‐4, 5, 9, 10‐tetraone (PTO) anode. The co‐insertion of H2 O molecules and proton into the PTO organic anode effectively reduces the interfacial resistance between the anode and electrolytes, and achieves an unprecedented rate capability up to 250 C and as short as 7 s per charge/discharge. A PTO‐based full cell exhibits an outstanding power density (>104 W kg −1 ) comparable to supercapacitors. The full utilization of the four C=O groups in PTO molecule during cycling enables the highest capacity (85 mAh g −1 ) reported for proton batteries to date. This study represents a significant leap forward in the exploitation of ultrafast electrochemical energy storage and accelerates the development of intermittent grid‐scale energy storage technologies. Abstract : The co‐insertion of H2 O and proton into the pyrene‐4, 5, 9, 10‐tetraone (PTO) organic electrodes can decrease the desolvation energy penalty and shield the proton charges at the electrolyte–electrode interface, leading to the fast diffusion of proton at the interface.